Legal Protection of Patients' Rights on the Recording Action Camerating or Photographing in the Hospital - Iga Pamungkas; Dwi Hapsari Retnaningrum; Setya Wahyudi (Riviera Publishing, 2025)
The regulation of health services in Indonesia has been subject to heightened oversight in accordance with Law No. 17 of 2023 concerning Health. This legislative act encompasses provisions for the delivery of health services, in addition to the establishment of legal safeguards for patient rights. Among the rights protected by this legislation are the rights to privacy, confidentiality, and access to information. This study analyzes the legal dimensions that focus on cases in hospitals. The present study examines the legal protection of patient rights with regard to the act of recording or photographing without permission in the hospital. The aim of the study is to provide recommendations to strengthen patient privacy protection and more effective law enforcement. The study employs an empirical legal method, which involves the examination of normative legal provisions and the collection of primary data directly from the field through surveys, interviews, and field reports. The results of the study indicate that certain legal norms are not being implemented effectively. For instance, the rules in each area prohibit photography without authorization, and the hospital has established accountability measures for individuals who take pictures or record activities without permission. These individuals may be subject to sanctions.